UNDERESTIMATION OF HEAT RELEASE FROM THE EARTH'S INTERIOR IN THE BAIKAL RIFT ZONE USING TRADITIONAL METHODS OF GEOTHERMICS - Golubev V.A. (My University, 2003)
The interrelation between conductive and convective (hydrothermal) components of heat release was not taken into account in the previous interpretations of the thermal anomaly in the Baikal rift zone (BRZ). In this communication we show that consideration of this component leads to a revision and significant augmentation of the estimates of thermal losses in the Earth's crust of the BRZ.